Natural Compounds Tapinarof and Galactomyces Ferment Filtrate Downregulate IL-33 Expression via the AHR/IL-37 Axis in Human Keratinocytes - Tsuji, Gaku; Hashimoto-Hachiya, Akiko; Matsuda-Taniguchi, Tomoyo; Takai-Yumine, Ayako; Takemura, Masaki; Yan, Xianghong; Furue, Masutaka; Nakahara, Takeshi (Frontiers in Immunology, 2022)
Interleukin (IL)-37 suppresses systemic and local inflammation. It is expressed in the epidermis, the external layer of the skin, and is decreased in inflammatory skin diseases including atopic dermatitis (AD) and psoriasis. Therefore, an agent applied topically on the skin that can increase IL-37 could be promising for treating AD and psoriasis; however, the mechanism regulating IL-37 remains largely unknown. Given that IL-37 expression is induced in differentiated keratinocytes, a major component of the epidermis, and that activation of aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, promotes keratinocyte differentiation, we hypothesized that AHR might be involved in the IL-37 expression in human keratinocytes. We analyzed normal epidermal human keratinocytes (NHEKs) treated with tapinarof and Galactomyces fermentation filtrate (GFF), which are potent AHR modulators. We found that tapinarof and GFF upregulated IL-37 in NHEKs, which was canceled by the knockdown of AHR using siRNA transfection, indicating that AHR mediates IL-37 expression in NHEKs. Furthermore, we found that the knockdown of IL-37 resulted in the upregulation of IL-33, an alarmin cytokine with crucial roles in the pathogenesis of AD and psoriasis. These findings suggest that IL-37 negatively regulates IL-33 expression in NHEKs. Finally, we examined whether tapinarof and GFF treatment modulates IL-33 expression in NHEKs. Such treatment inhibited IL-33 expression, which was partially reversed by the knockdown of either AHR or IL-37. Taken together, our findings provide the first evidence that tapinarof and GFF could have potential to prevent IL-33-overexpressing disorders such as AD and psoriasis via the AHR/IL-37 axis.